Relationship between hyperuricemia and erectile dysfunction on hypertension patients - Vera Ticoalu, Jansje Henny; Kandarina, Istiti; Rizal, Dicky Moch.; Pramantara Setiabudi, I Dewa Putu (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Hypertension is a major non-communicable disease worldwide including in Indonesia. It can cuase erectile dysfunction through vasculogenic pathway. Uric acid level could be a promising biomarker to predict erectile dysfunction due to it is related to endothelial dysfunction, microvascular disease, and hypertension. The aim of this study was to evaluate the relationship between hyperuricemia and erectile dysfunction on hypertension patients. This was an observational study with cross-sectional design involving 88 male hypertension patients aged more than 18 years who registered as outpatient in the Bethesda Lempuyangwangi Public Hospital, Yogyakarta. Hyperuricemia was measured using uricase method and erectile dysfunction was measured using IIEF-5 form. The results showed that hyperuricemia (OR=3.89; CI 95% 1.08-15.70; p=0.017), blood pressure (OR=6.84; CI 95% 2.35-20.6; p<0.001), and age (p<0.001) are related with erectile dysfunction on the hypertension patients. Furthermore, logistic regression analysis showed that hyperuricemia, age, and blood pressure simultaneously affect the erectile dysfunction occurance, with good calibration (p=0.167) and discriminative level (0.8604). In conclusion, there is significantly relationship between hyperuricemia and erectile dysfunction on hypertension patients.